Sports, morality and body: The voices of sportswomen under Franco's dictatorship. (September 2016) - Pujadas, Xavier; Garai, Beatriz; Gimeno, Fernando; Llopis-Goig, Ramón; Ramírez-Macías, Gonzalo; Parrilla-Fernández, José M
The aim of this research is to study sportswomen's perceptions and experiences of women's sport in Francoist Spain (1939–1975). The main objective is to analyse the social, moral and aesthetic elements that are present in the experience of these athletes. This study was carried out with an intentional sample of 24 women from Andalusia, Aragon, Asturias, Basque Country, Catalonia and Valencia. They were interviewed by a network of researchers from six universities. Outstanding results show the existence of social limitations to start sports practice (particularly in the post-war period); the importance of sport as a character-building aspect; sport's remarkable influence on their body self-concept; and the incidence on sports of the mainstream moral discourse, which created a female model that even affected sports clothing. The main conclusion is that sportswomen in that period were pioneers and had to fight against most of society in order to develop their facet as athletes, as they would not follow the established model.